2011
DOI: 10.5334/ijic.665
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a continuum of care model for older people - results from a Swedish case study

Abstract: IntroductionThere is a need for integrated care and smooth collaboration between care-providing organisations and professions to create a continuum of care for frail older people. However, collaboration between organisations and professions is often problematic. The aim of this study was to examine the process of implementing a new continuum of care model in a complex organisational context, and illuminate some of the challenges involved. The introduced model strived to connect three organisations responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 29 publications
5
36
0
3
Order By: Relevance
“…In line with previous research [5253], having adequate organizational support, i.e. policy strategies enabling co-leadership as a management solution throughout the organization, and having clear common objectives for the services were emphasized as key pre-conditions.…”
Section: Discussionsupporting
confidence: 57%
“…In line with previous research [5253], having adequate organizational support, i.e. policy strategies enabling co-leadership as a management solution throughout the organization, and having clear common objectives for the services were emphasized as key pre-conditions.…”
Section: Discussionsupporting
confidence: 57%
“…The study is part of a larger multidisciplinary project entitled Continuum of Care for Frail Elderly People (Hasson , Dunér et al . , Wilhelmson et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Organizational obstacles, such as lack of interest on the part of management, have been reported in several studies (Bryar et al, ; Hannes et al., ; McCormack et al, ; Rycroft‐Malone et al, ). It has been argued that one prerequisite for organizational support is that interventions match the priorities and strategies selected by management (Duner, Blomberg, & Hasson, ; Røsstad et al, ) and that this match (or lack thereof) may serve as a way to predict and control the work environment (Habermas, ). In our study, this was demonstrated by the finding indicating that management support was a principle feature, but for successful implementation to occur, the project had to be given priority over other projects.…”
Section: Discussionmentioning
confidence: 99%